Surface coloration of Zr-based metallic glass by nanosecond pulsed laser irradiation in ambient atmosphere - Zhang, Hongyang; Qian, Yongfeng; Zhang, Lin; Zhang, Di; Liu, Hanlin; Huang, Hu (Materials Letters, 2021)
•Surface coloration of Zr-based metallic glass was achieved by nanosecond laser irradiation.•Four kinds of surface color were successfully produced.•The irradiated surfaces were covered by the laser scanning tracks and micro/nanoscale particles.•The coloring mechanism was discussed according to the surface characteristics. Coloring the surface of metallic glasses (MGs) would be beneficial to their industrial and commercial applications. In this study, by nanosecond pulsed laser irradiation in ambient atmosphere, four kinds of surface color were successfully achieved for a typical Zr-based MG. All these four colorated MG surfaces mainly included two kinds of microstructures, i.e., the laser scanning tracks and micro/nanoscale particles. The chemical compositions of these four laser-irradiated surfaces were further characterized by X-ray diffraction (XRD), X-ray electron spectroscopy (XPS), and energy dispersive X-ray spectroscopy (EDS). The results indicated that kinds of oxides were formed on the irradiated surfaces. According to the XRD, EDS and XPS results, the cross-sectional characteristics as well as the comparative experiments in argon atmosphere, the surface color could be attributed to the interference of oxide films with different thicknesses. This study provides a simple and low-cost method for coloring MGs, which is expected to broaden their functional applications.